ANAEROBIC TREATMENT OF WATER WITH REFRIGERATOR USE OF WASTEWATER DIGESTERS: USE OF BIOLOGICAL REMEDIATION FOR PRODUCTION OF BIOGAS - Da Costa, L.V.C.; Moghrabi, J.A.; Sagula, A.L.; Junior, J. De L. (Revista Brasileira de Engenharia de Biossistemas, 2013)
Cattle slaughter generate large amounts waste due to its high concentration of organic matter (presence of fats and proteins), should receive treatment before disposal, even being considered harmful to the environment while these residues may have a good potential for reuse of biogas production. Aimed at producing biogas and appropriate treatment for such wastes this work is to evaluate the inclusion of bioremediators in the process of anaerobic digestion of wastewater fridge batch digesters. Production and quality of biogas, pH, levels of total (TS) and volatile solids (VS) solids and hydraulic retention time was analyzed. Four treatments were considered: T1- Control + wastewater + T2- control remedial wastewater 1, T3 - Control + wastewater + remedial + 2 and T4- control wastewater remediation + 1 and 2. The results show that there was no difference between treatments for the production of biogas, but the treatment 3 was the first to introduce burns, indicating the presence of methane.